ANALISIS KEMANDIRIAN BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA DITINJAU DARI GENDER - Setiawan, Adi; Sujiwo, Dimas Anditha Cahyo; Panglipur, Indah Rahayu (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
This study aims to describe students' learning independence in mathematics learning in terms of gender. Learning uses the drill method, namely repeating seriously with the aim of understanding what is being learned. The research method used is descriptive qualitative. The research instrument uses a questionnaire to measure students' mathematics learning independence and interviews are used as additional instruments to obtain more in-depth information about students' experiences and views on their learning independence. The research subjects were 12 female and 12 male students of class VII of SMP Kartika IV-6 Ambulu. The data analysis technique used involved the use of a percentage formula for student answers based on indicators of student learning independence, which were then described using the criteria for interpreting the percentage of answers. The results of the study showed that student independence in mathematics learning in terms of gender showed that males had an average of 59.03% with the category of "mostly" independent and females had an average of 63.19% with the category of "mostly" independent. Based on the results of the percentage, most male and female students are able to learn independently.